Teachers' Challenges in Differentiated Social Studies Learning Implementation in Junior High Schools in Jepara Regency - Safitri, Dia Nita Ayuk; Suharini, Erni; Arsal, Thriwaty (Journal of Educational Social Studies, 2025)
The central gap in implementing differentiated learning lies in the mismatch between curriculum demands and practices caused by limited understanding, resources, time, policy support, and adaptive evaluation. This research aimed to identify teacher preparation, analyze the obstacles, and identify teachers' efforts in implementing differentiated social studies learning in the Merdeka Curriculum at SMP Negeri 1 Bangsri and MTS Hasyim Asy'ari. Researchers use qualitative methods which produce qualitative descriptive data through in-depth interviews, observation and documentation. The key informant in the research is the social studies teacher. The findings showed that the teachers' efforts in implementing differentiated learning were by attending training provided by the school and the government and then making teaching modules according to the student's needs. The significant obstacles faced are time limitations, lack of understanding and facilities, and the use of technology that has yet to be optimal. The efforts made by teachers are using various learning strategies, utilizing media and methods in differentiated learning, and selecting effective assessments and evaluations such as summative and formative assessments. This research suggests that increasing teacher training, providing additional facilities at school, and optimizing school support are crucial to ensure the successful implementation of differentiated social studies learning.